Web-based physical activity intervention for people with progressive multiple sclerosis: application of consensus-based intervention development guidance. Issue 3 (16th March 2021) - Busse, Monica; Latchem-Hastings, Julie; Button, Kate; Poile, Vince; Davies, Freya; O' Halloran, Rhian; Stensland, Barbara; Tallantyre, Emma; Lowe, Rachel; Wood, Fiona; Dawes, Helen; Edwards, Adrian; et al.
Abstract : Objectives: People with progressive multiple sclerosis (PwPMS) report that they recognise the benefits of activity on their physical and psychological health but need support to achieve their physical activity goals. We aimed to systematically develop a theoretically informed intervention that would enable PwPMS to more readily engage in regular physical activity. Design: We used an intervention mapping approach to inform intervention development. Setting: We conducted semistructured interviews with PwPMS and their families/carers and physiotherapists recruited from secondary care settings. Participants: Fourteen PwPMS with an Expanded Disability Status Scale score of between 6 and 8 and 7 of their families/carers and 13 physiotherapists and 1 physiotherapy technician participated. Results: Interview data suggested that the development of supportive coaching relationships with physiotherapists could promote the ability of PwPMS to achieve a desirable and achievable physical activity plan. These interview data informed the prototype 'Lifestyle Exercise and Activity Package for Multiple Sclerosis' (LEAP-MS) consisting of a secure multiuser web-based platform (with an education and activity suite, interactive components enabling selection of exercises, goal setting and activity logging), up to six flexible face-to-face or web-based physiotherapy coaching sessions and remote support via an embedded web-based messaging function that all together draw on specific theory-based methods to achieve physical activity behaviour change, namely active learning, reinforcement, modelling, feedback, facilitation, goal setting and guided practice. Implementation is within a multiuser platform accessible to participants, trained physiotherapists and researchers. Conclusions: We have followed an inclusive, systematic and transparent process to develop the LEAP-MS intervention that enables detailed description of components, context and guiding principles to inform ongoing evaluation. Importantly, PwPMS expressed the need for autonomy in developing physical activity plans. This has been achieved through the embedding of self-management principles in the design and delivery of the LEAP-MS intervention.